2020
DOI: 10.1111/head.13836
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet and Nutrition in Migraine Triggers and Treatment: A Systematic Literature Review

Abstract: Background.-Migraine is a disabling primary headache disorder often associated with triggers. Diet-related triggers are a common cause of migraine and certain diets have been reported to decrease the frequency of migraine attacks if dietary triggers or patterns are adjusted. Objective.-The systematic literature review was conducted to qualitatively summarize evidence from the published literature regarding the role of diet patterns, diet-related triggers, and diet interventions in people with migraine. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
117
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 67 publications
1
117
0
2
Order By: Relevance
“…Evaluating the role of diet in migraine is complex because multiple triggers and variables can modify the pain threshold in an individual, and this factor is frequently neglected in favor of preventive drug therapy for pediatric patients [ 75 ]. Although chocolate is the most frequent dietary trigger for migraines in children [ 23 , 74 ], a recent review article found insufficient evidence of chocolate being described as a definitive migraine trigger [ 76 ].…”
Section: Prevalence Of Trigger Factors In Migrainementioning
confidence: 99%
See 2 more Smart Citations
“…Evaluating the role of diet in migraine is complex because multiple triggers and variables can modify the pain threshold in an individual, and this factor is frequently neglected in favor of preventive drug therapy for pediatric patients [ 75 ]. Although chocolate is the most frequent dietary trigger for migraines in children [ 23 , 74 ], a recent review article found insufficient evidence of chocolate being described as a definitive migraine trigger [ 76 ].…”
Section: Prevalence Of Trigger Factors In Migrainementioning
confidence: 99%
“…Current research on adults shows that high folate diets, low-fat diets, low-sodium diets, foods high in high omega-3 fatty acids, and ketogenic diets are effective in reducing migraines [ 79 , 80 ]. However, there is a lack of scientific evidence to support these diets as a therapeutic recommendation [ 75 ]. Even chocolate lacks sufficient evidence of being labeled a proper trigger, as per a recent systematic review [ 76 ].…”
Section: Prevalence Of Trigger Factors In Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…21 In the following sections, some examples from the current literature are presented to highlight what we already know about the effects of diet on migraine and the effects of migraine on dietary choices, and what remains unknown to stimulate further research. Therefore, the purpose of this targeted review is not to provide a comprehensive systematic review of the current literature on the role of diet in migraine; since several excellent reviews are already available (eg, 9,[22][23][24][25][26] ). PubMed, Cochrane Library, EMBASE, and Web of Science databases were searched for studies using keywords of diet, migraine, food, and lifestyle with the aim of providing the current overview, and a viewpoint to the potential future directions.…”
Section: Introductionmentioning
confidence: 99%
“…This type of primary headache usually presents with recurrent, typically unilateral and pulsating attacks of severe headaches, lasting from 4 to 72 h, with accompanying symptoms including photophobia, phonophobia, nausea, and vomiting [ 3 ]. Caffeine has been linked with migraine for many years, on the one hand as a trigger, and on the other as a cure [ 4 , 5 , 6 , 7 , 8 ]. As most of the population, including migraine sufferers, consume a considerable amount of coffee and other caffeinated drinks and foods daily, a question arises as to whether it influences their headaches.…”
Section: Introductionmentioning
confidence: 99%